On the existence and location of cardiac mucosa: an autopsy study in embryos, fetuses, and infants. Issue 6 (1st June 2003) - De Hertogh, G; Van Eyken, P; Ectors, N; Tack, J; Geboes, K
Abstract : Background: The incidence of gastric cardiac adenocarcinoma has increased in the last decades. Gaining insight into the pathogenesis of this lesion is hampered by the limited knowledge of the origin and histology of cardiac mucosa (CM). Currently, the location, extent, and even the existence of CM are controversial. Aims: We studied the development of the gastro-oesophageal junction (GOJ) in embryos, fetuses, and infants to clarify if CM is a normal structure at birth and where it is located. Subjects: Twenty one autopsy cases were evaluated ranging in age from 13 weeks' gestational age (GA) to seven months. Methods: The distal oesophagus and proximal part of the stomach were embedded entirely. Serial sections were stained with haematoxylin-eosin and alcian blue/periodic acid-Schiff. The following parameters were measured: length of abdominal oesophagus; length of columnar lined oesophagus; length of CM; and distance from CM to angle of His. Results: CM was present in all evaluated sections. Its mean length varied throughout gestation. A maximum value was reached at a GA of 16 weeks (1.2 mm). After term delivery it was very short (0.3–0.6 mm). CM was proximal to, or straddled, the angle of His in all cases. During gestation, the mucin staining pattern of the CM was to a high degree similar to that of the developing pyloric mucosa. Conclusions: CM develops during pregnancy and is present at birth as a normal structure. If the angle of His is taken as a landmark for the GOJ, CM is located in the distal oesophagus.